Krisis Keuangan Masa Depan dan Sistem Keuangan Baru - Anggi Pratiwi Sitorus; Mahlel; M. Shabri A. Majid; Marliyah; Rita Handayani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
The financial crisis is basically a condition of the economy experiencing a rapid decline caused by the demand for money that exceeds the supply of money due to the occurrence of a large bank rush. In order to seek more accurate monitoring and review of the stability of the banking system and national financial system in order to avoid the recurrence of systemic risk, in the event that the supervisory and supervisory duties of banks have been separated from Bank Indonesia, then Bank Indonesia as the central bank needs to be authorized to be able to directly access reliable data in the banking sector. The study uses a descriptive qualitative approach with research findings that the impact of the crisis on the economy has proven to have a bad impact on the Indonesian economy and as has been explained that the economic crisis, especially the financial crisis, has a repeating period, meaning that if a country has ever been affected by an economic crisis, it will not be affected by the economic crisis. the country will soon be free from the economic crisis because it might happen again. And financial system stability is a condition in which economic mechanisms in pricing, allocation of funds, and risk management function properly and support economic growth.